The Role of Head Elevation in Treatment of Vitreous Haemorrhage - Pongsachareonnont P; Rattana-aram N; Somkijrungroj T (Clinical Ophthalmology, 2020)
Pear Pongsachareonnont, Nattadet Rattana-aram, Thanapong Somkijrungroj Vitreoretinal Research Unit, Department of Ophthalmology, Faculty of Medicine, Chulalongkorn University and King Chulalongkorn Memorial Hospital, Thai Red Cross Society, Bangkok, ThailandCorrespondence: Pear PongsachareonnontDepartment of Ophthalmology, King Chulalongkorn Memorial Hospital, 1873 RamaIV Road Payathai, Bangkok 10330, ThailandTel +66 2 256 4144 ext 0Email pear.p@chulahospital.orgObjective: To investigate the effect of head elevation on macular clearance of acute vitreous haemorrhage.Design: Crossover, prospective, randomized clinical study.Setting: University, tertiary care hospital.Participants: 24 vitreous haemorrhage patients, average age 55 years.Methods: Patients with acute vitreous haemorrhage who were randomly separated into 2 groups. In group A, the patients were assigned normal head position for the first week of sleep, then switched to head elevation for the second week (n=12). In group B, the patients were assigned the head position in reverse order (n=12). A washout period of 24 hrs was used between treatments. The carryover, sequence, and treatment effects were analysed by using various mixed models.Outcomes: Best-corrected visual acuity (BCVA), vitreous haemorrhage grading, fundus photo colour intensity, and self-assessment scores.Results: Although the mean BCVA (LogMAR) change following head elevation was higher than following normal head position, the difference was not statistically significant (−0.053 and 0.065 LogMAR, respectively, p = 0.2). Vitreous haemorrhage grading in the central region showed no statistical improvement in either group. Fundus photo colour intensity comparison in all fundus areas also showed no statistically significant differences in either group.Conclusion: Although head elevation is recommended to patients with acute vitreous haemorrhage, this study showed no statistically significant improvement in BCVA, vitreous haemorrhage grading, or fundus photo colour intensity between head elevation and normal head position in the early observation period.Trial registration: TCTR20150314001.Keywords: vitreous haemorrhage, head elevation, visual acuity, fundus colour intensity